Gentamicin-releasing urethral catheter for short-term catheterization - Cho, YW; Park, JH; Kim, SH; Cho, YH; Choi, JM; Shin, HJ; Bae, YH; Chung, H; Jeong, SY; Kwon, IC (VSP BV, 2003)
Urethral catheters, widely used for the drainage of the bladder, are associated with most urinary tract infections (UTIs) that account for 40% of all episodes occurring in acute-care hospitals. This study aimed to develop a gentamicin-releasing catheter that effectively prevents UTIs for short-term catheterization. For physical loading of gentamicin, the urethral catheters were coated by the simple dipping method with poly(ethylene-co-vinyl acetate) (EVA) and EVA/poly(ethylene oxide) (PEO) blends containing gentamicin. By varying the molecular weight (MW) and contents of PEO in the blends, various catheter surfaces were produced. In vitro drug release studies demonstrated that all the coated catheters exhibited sustained release up to 7 days; however, the release pattern was significantly dependant on the coating layers. Of the coated catheters, EVA/PEO (MW = 100k)-coated catheters were utilized to evaluate the antibacterial activity using an inhibition zone test, since they showed a promising drug release behavior and had PEO-rich biocompatible surfaces. In accordance with drug release behavior, EVA/PEO-coated catheters exhibited antibacterial activities for 7 days against Proteus vulgaris, Staphylococcus aureus and Staphylococcus epidermidis. These results imply that the catheters coated with EVA/PEO have a potential for short-term catheterization.
Keywords: URINARY-TRACT INFECTIONS; COPOLYMER/SEGMENTED POLYURETHANE BLENDS; PDMS-BASED POLYURETHANES; PLATELET-ADHESION; MPEG GRAFTS; PREVENTION; COLONIZATION; EPIDEMIOLOGY; BACTERIURIA; MORBIDITY